PENERAPAN PENDEKATAN KETERAMPILAN PROSES IPS DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS III DI SDN KALISALAM II - Rosalina Agustin; Adetegar Youliyan Primadani; Vivin Handayani (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2022)
Social studies lessons are known as boring lessons because the delivery method is like a lecture, therefore students' interest in social studies lessons is very different from counting, reading or skills lessons. This article aims to discuss how to attract student involvement by using the IPS process skills approach. The method used is the preparation of a Learning Implementation Plan (RPP) made by the teacher correctly and the components are complete. The results of this article, if the skills of the learning process are said to be successful, if students are able to complete test questions or exams by obtaining good grades.Keywords: IPS process skills